Biomechanics of Flexion and Extension Spinal Injury: A Study of AOSpine Thoracolumbar Fracture Type B - Zubaedi, Alisha Chaerani; Rachman, Amanda Azkiyah; Hardiant, Excell Defry; Mikailla, Romy Healthy; Priyanto, Bambang (Jurnal Biologi Tropis, 2025)
The thoracolumbar junction is highly vulnerable to injury due to its transitional biomechanics. Flexion-distraction and extension-distraction forces commonly produce AOSpine Type B injuries. To describe the biomechanics of thoracolumbar flexion and extension injuries and summarize AOSpine Type B fracture mechanisms. A narrative literature review was conducted using scientific articles, textbooks, and AOSpine guidelines focusing on thoracolumbar anatomy, biomechanics, and Type B injury mechanisms.  AOSpine Type B injuries result from tension band failure. Flexion-distraction (B1-B2) disrupts posterior structures, whereas extension-distraction (B3) causes anterior tension band failure, often influenced by spinal rigidity or high energy trauma. Understanding biomechanical mechanisms of AOSpine Type B injuries is essential for accurate classification and guiding management decisions.